Arsitektur Enterprise Aplikasi SIP Menggunakan Kerangka Kerja Zachman - Sugiyanto, Yanto; Shofia Hilabi, Shofa; Huda, Baenil (Universitas Samudra, 2024)
The Pension Information System (SIP) is a digital platform specifically designed for comprehensive and transparent management of pension information. In modern administration, administrative efficiency and transparency are very important to improve the quality of public services. Therefore, the development of an appropriate pension information system (SIP) has a strategic role in increasing the productivity and work efficiency of civil servants. Enterprise application architecture has become an important element in the development of complex information systems. In this research, we investigate the application of the Zachman framework to the architectural design of enterprise pension information system (LIS) applications. Research methods include documentary analysis and interviews with experts in the field of software architecture. Our research results show that the application of the Zachman framework provides an organized and clear structure to the architectural design of enterprise pension information system (LIS) applications. By considering the various aspects provided by the Zachman framework, the architectural design process can be carried out systematically and efficiently. It is hoped that this research can contribute to the development of a company application architecture design methodology, especially those related to the implementation of pension information systems (SIP). The findings of this research also encourage further research regarding the application of new technology to support information system integration at the agency level.